Mind over matter: mindfulness as a buffer against workplace incivility - Huseynova, Gonchakhanim; İslamoğlu, Mehmet (Frontiers in Psychology, 2024)
This study examines the relationship between co-worker incivility, emotional exhaustion, mindfulness, and turnover intention among nurses in public and private hospitals in North Cyprus. Drawing upon the Job Demand-Resources theory, the research aims to contribute to the existing literature by investigating the mediating role of emotional exhaustion and the moderating effect of mindfulness on the relationship between co-worker incivility and turnover intention. Data were collected from 238 nurses through questionnaires, and structural equation modeling was employed for data analysis. The results indicate a positive association between co-worker incivility and emotional exhaustion, as well as between coworker incivility and turnover intention. Emotional exhaustion was found to mediate the relationship between co-worker incivility and turnover intention. Furthermore, mindfulness was identified as a moderator, attenuating the negative impact of co-worker incivility on turnover intention. The findings underscore the importance of addressing workplace incivility and promoting mindfulness to mitigate turnover intentions among nurses. Practical implications include the implementation of interventions to foster a supportive work environment and enhance nurses' emotional well-being.